Cover Picture: Simultaneously Sizing and Quantitating Zeptomole‐Level DNA at High Throughput in Free Solution (Chem. Eur. J. 43/2014). Issue 43 (20th October 2014) - Zhu, Zaifang; Chen, Huang; Chen, Apeng; Lu, Joann J.; Liu, Shaorong; Zhao, Meiping
<x xml:space="preserve">Abstract</x> Size determination and measurement of the quantities of DNA molecules are fundamental tasks in molecular biology. A new technique, called bare‐narrow‐capillary/hydrodynamic‐chromatography or BaNC‐HDC, has been developed for resolving DNA molecules based on their sizes without using any sieving matrices. For more details, see the Full Paper by S. Liu, M. Zhao et al. on page 13945 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>